Informational literature influences symptom expression following mild head injury: An analog study. (August 2015) - Waldron-Perrine, Brigid; Tree, Heather A.; Spencer, Robert J.; Suhr, Julie; Bieliauskas, Linas
Abstract Primary objective: Many Veterans involved in recent OEF/OIF conflicts return with reports of having experienced an mTBI. The Veteran's Affairs (VA) and Department of Defense (DoD) have gone to great lengths to provide information to Veterans regarding possible effects of TBI. Although well intended, this information may possibly have an iatrogenic effect. Conversely, setting positive expectations for recovery from mTBI has been shown to result in decreased symptomatology. Research design: One-way ANOVA and Tukey post-hoc analyses were used to determine whether there were significant differences on reported severity and number of PCS symptoms (NSI) among the three experimental groups (recovery focused information; expectation for persistent symptoms; and no information given). Methods and procedures: Undergraduate students, who were told to imagine they had experienced a military-related TBI, reported varying levels of expected symptoms when given either positive or negative information about symptom expectation. Main outcomes and results: The results indicate that presenting recovery-oriented literature resulted in the lowest report of expected symptoms, whereas presenting no information resulted in the highest report of expected symptoms. Conclusions: Providing Veterans with information regarding a likely positive trajectory of recovery may result in less symptom persistence during rehabilitation.